Supporting enterprise globally : policy paper (ACCA LondonGB, 2009)
Recognises the importance of small and medium sized enterprises across the world and outlines ACCA's experience of working with the sector. Outlines some of the key issues that should be high upon the SME agenda of governments, regulators, and standard setters across the world.
Keywords: SMALL ENTERPRISES